Box-Behnken Experimental Design Aided Optimization of Stability Indicating HPTLC-Based Assay Method: Application in Pharmaceutical Dosage form Containing Model Drugs-Roxithromycin and Ambroxol Hydrochloride. Issue 6 (2nd November 2019) - Patel, Rashmin B.; Patel, Mrunali R.; Patel, Nilay M.
Abstract: The objective of this study was to apply Design of Experiment (DoE) concept for development of stability indicating high-performance thin-layer chromatography (HPTLC) method for assay of model drugs (Roxithromycin (ROXTM) and Ambroxol hydrochloride (AMBRX)) in marketed tablet formulations followed by validation of developed HPTLC method as per ICHQ2(R1). Box-Behnken experimental design was applied to optimize chromatographic conditions and their effects on retardation factor (Rf) value. The developed HPTLC method was validated for specificity, linearity, accuracy, precision, and robustness. The ROXTM (Rf 0.42) and AMBRX (Rf 0.75) were well separated (Rs 2.06) from each other and from their respective degradation products on HPTLC plate using optimized chromatographic conditions. The developed method was successfully validated and statistical analysis proved that the method is sensitive, specific (peak purity > 0.9999 for both ROXTM and AMBRX), accurate (98.59-101.14 % and 99.96-101.76 %, ROXTM and AMBRX, respectively) and precise (% RSD >1.0 for both ROXTM and AMBRX). The developed HPTLC method have advantages over reported methods in being robust and able to determine the model drugs and degradation products with sensitivity, selectivity and short analysis time using simple mobile phase.